Synergistic formation of samarium oxide/graphene nanocomposite: A functional electrocatalyst for carbendazim detection. (November 2022) - Sakthi Priya, Thangavelu; Nataraj, Nandini; Chen, Tse-Wei; Chen, Shen-Ming; Kokulnathan, Thangavelu
Abstract: Herein, an electrochemical sensor based on samarium oxide anchored, reduced graphene oxide (Sm2 O3 /RGO) nanocomposite was developed for the rapid detection of carbendazim (CBZ). Different characterization methods were infused to deeply examine the morphology, composition, and elemental state of Sm2 O3 /RGO nanocomposite. The Sm2 O3 /RGO modified electrode exhibits an excellent electro-catalytic performance toward CBZ detection with a peak potential of +1.04 V in phosphate buffer solution (pH 3.0), which is superior to the RGO–, Sm2 O3 – and bare– electrodes. This remarkable activity can be credited to the synergetic effect generated by the robust interaction between Sm2 O3 and RGO, resulting in a well-enhanced electrochemical sensing ability. Impressively, the fabricated sensor shows improved electrochemical performance in terms of the wide working range, detection limit, and strong sensitivity. On a peculiar note, the electrochemical sensing performances of CBZ detection based on Sm2 O3 /RGO nanocomposite demonstrate an extraordinary behavior compared to the prior documented electro-catalyst. In addition, the fabricated Sm2 O3 /RGO sensor also displays good operational stability, reproducibility, and repeatability towards the detection of CBZ. Furthermore, it was successfully applied to the CBZ detection in food and environmental water samples with satisfactory recovery. In accordance with our research findings, the Sm2 O3 /RGO nanocomposite could be used as an electro-active material for effectual electrochemical sensing of food and environmental pollutants. Graphical abstract: Image 1 Highlights: The Sm2 O3 /RGO nanocomposite was successfully synthesized. The Sm2 O3 /RGO nanocomposite was used for electrochemical detection of CBM. It can exhibit good analytical performance for the detection of CBM. The proposed sensor has been tested for determined CBM in actual samples.